Guidance and Development of Learning Models in the Pandemic Era for students with Special Needs through Blended Learning at the Kevala Cibarusah Inclusive School - Badrianto, Yuan; Ekhsan, Muhamad; Kurnia, Santi (Central Community Development Journal, 2021)
Inclusive schools are educational services provided for children with special needs (ABK) in obtaining a better education. Coaching needs to be carried out on inclusive school teachers by increasing the competence of teachers because learning with special needs children has different obstacles and challenges. The method used is to provide motivational training to teachers and make learning administration and apply the blended learning model. With the guidance and development of the blended learning model, teachers feel that they work more effectively when compared to online only, which is relatively difficult for children with special needs, this is due to the limited response of ABK, different and easily distracted. With blended learning, children can learn to adapt to the demands of technology but also still get exclusive services from teachers and thearpists.